2005
DOI: 10.1002/ffj.1700
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual differences between chemical stimuli presented through the ortho- or retronasal route

Abstract: Orthonasal or retronasal presentation of certain odours in everyday life, such as cheese or fish, evokes different responses. To study this phenomenon, stimulation techniques were developed to allow ortho-or retronasal presentation of chemosensory stimuli. Based on this technique, several studies were performed to investigate: (a) the subjects' ratings of stimulus intensity, hedonic characteristics of the stimuli, and stimulus quality; (b) the peripherally obtained electro-olfactogram; (c) EEG-derived olfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 43 publications
3
42
0
Order By: Relevance
“…Odorant molecules of the aliment could indeed reach the olfactory epithelium either via the nose (orthonasal olfaction) or via the nasopharynx when food is introduced into the mouth (retronasal olfaction) during eating and drinking (Pierce and Halpern, 1996). Psychophysical data indicate that the same odor delivered through the two routes could have different perceptual qualities (Rozin, 1982;Sun and Halpern, 2005;Hummel et al, 2006). This assumption was recently supported by dissimilarities in functional MRI brain activations (Small et al, 2005) and in event-related potentials (Hummel and Heilmann, 2008) according to orthonasal or retronasal odorant stimulations.…”
Section: Introductionmentioning
confidence: 92%
“…Odorant molecules of the aliment could indeed reach the olfactory epithelium either via the nose (orthonasal olfaction) or via the nasopharynx when food is introduced into the mouth (retronasal olfaction) during eating and drinking (Pierce and Halpern, 1996). Psychophysical data indicate that the same odor delivered through the two routes could have different perceptual qualities (Rozin, 1982;Sun and Halpern, 2005;Hummel et al, 2006). This assumption was recently supported by dissimilarities in functional MRI brain activations (Small et al, 2005) and in event-related potentials (Hummel and Heilmann, 2008) according to orthonasal or retronasal odorant stimulations.…”
Section: Introductionmentioning
confidence: 92%
“…This difference might be expected, given participants' inability to evaluate products based on appearance, taste, flavour and texture when evaluating the product based on odour only. Previous observations have shown that certain foods appear to be sensed differently, depending on the mode of presentation (Hummel et al, 2006). In their study attention was drawn to the interaction between the chemosensory modalities (i.e.…”
Section: Consumer Freshness Evaluationsmentioning
confidence: 99%
“…Odor is sensed orthonasally, while aroma is sensed retronasally (1). It has been reported that the perception of volatile compounds by the two routes is different (2,3). This has been explained by the need for humans to use the sense of smell in two different ways.…”
mentioning
confidence: 99%